At-risk students : portraits, policies, programs, and practices - Donmoyer, Robert; Kos, Raylene (SUNY series, youth social services, schooling, and public policy., 1993)
Annotation Explores the circumstances of at-risk students and argues that well- intentioned policymakers and educators run the risk of making matters worse rather than better for these students. The volume demonstrates the diverse, idiosyncratic nature of these students, argues that traditional social science methods cannot capture this idiosyncrasy and diversity, and presents research methods, policies, and programs that can accommodate student diversity. Annotation copyright by Book News, Inc., Portland, OR.